2016
DOI: 10.1016/j.matdes.2016.01.107
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the elastic properties of metakaolin-based geopolymer with its composition

Abstract: Geopolymer shows great potential as a construction material with low energy consumption and carbon oxide emission. Quantitatively assessment of elastic properties of a geopolymer and understanding the correlations with its composition and microstructure are therefore very important for its rational utilization. In the present investigation, two series of metakaolin-based geopolymer (MKG) were synthesized by controlling, respectively, mass ratio of alkali in activator to powders, namely the alkali equivalent (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…The geopolymer binder had an elasticity modulus of 7.2 GPa at room temperature and 0.3 GPa after exposure to 1200 • C. The modulus of elasticity in the prepared geopolymer binder was consistent with the previously published results (5-7.8 GPa) [58][59][60]. The highest elasticity modulus at laboratory temperature was found in the sample with the corundum content (34.6 GPa), followed by chamotte (29.9 GPa), cordierite (28.9 GPa), and quartz (26.8 GPa).…”
Section: Mechanical Propertiessupporting
confidence: 90%
“…The geopolymer binder had an elasticity modulus of 7.2 GPa at room temperature and 0.3 GPa after exposure to 1200 • C. The modulus of elasticity in the prepared geopolymer binder was consistent with the previously published results (5-7.8 GPa) [58][59][60]. The highest elasticity modulus at laboratory temperature was found in the sample with the corundum content (34.6 GPa), followed by chamotte (29.9 GPa), cordierite (28.9 GPa), and quartz (26.8 GPa).…”
Section: Mechanical Propertiessupporting
confidence: 90%
“…Alkali activated geopolymers have attracted increasing attention in recent years for their potential uses as construction materials and environmentally cementitious binders that would partly replace ordinary Portland cement (OPC) [ 1 , 2 ]. Studies have shown that geopolymers have excellent mechanical properties [ 3 ], such as high early strength and low shrinkage [ 4 , 5 ]. In addition, geopolymers also can be used as construction panels and fire resistant materials [ 6 ] for their characteristic light weight and thermal insulation properties [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The changes of strength and pore structure were the consequences of physico-chemical interactions among the metakaolin particles and alkaline activator. Because both the Si/Al ratio and the Na/Al ratio were optimally selected according to the literature data [17] and our previous work [19], all the MKG mortars showed high compressive strengths. Our data did not follow the observation that materials with higher capillary pore volumes have lower strengths [45].…”
Section: Roles Of the Materials' Compositionmentioning
confidence: 99%
“…The engineering performances of geopolymer materials are highly dependent on the material composition, synthesizing method, and curing scheme [10,11,[16][17][18][19]. Among these factors, the material composition may play the most important role, because it decisively impacts the material structures, mechanical properties, and durability performances.…”
Section: Introductionmentioning
confidence: 99%